2022
DOI: 10.3390/biomedicines10071481
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in the 3′-Untranslated Regions of SMAD5, FN3KRP, and RUNX-1 Are Associated with Recurrent Pregnancy Loss

Abstract: Recurrent pregnancy loss (RPL) is typically defined as two or more consecutive pregnancy losses prior to 20 weeks of gestation. Although the causes of idiopathic RPL are not completely understood, vascular development and glucose concentration were reported to correlate with the pregnancy loss. The TGF-β signaling pathway which plays a significant role in pregnancy is activated by the interaction between high glucose and SMAD signaling and affects the vascular cells. SMAD5 and RUNX-1 are involved in the TGF-β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In recent years, studies have focused on the genetic risk factors for RM. For instance, Kwon et al (2022) evaluated 388 patients with RM and 280 controls in Korea and revealed that the rs10515478 C>G polymorphism of the SMAD5 gene and the rs1046875 G>A polymorphism of the fructosamine 3 kinase‐related protein (FN3KRP) gene are associated with a lower risk of RM. A study conducted by Talwar et al (2022) suggests that the 844INS68 polymorphism of cystathionine beta‐synthase (CBS) combined with the A2756G polymorphism of 5‐methytetrahydrofolate‐homocysteine methyltransferase (MTR) is associated with over 2‐fold increased RM risk.…”
Section: Current Opinions On Rmmentioning
confidence: 99%
“…In recent years, studies have focused on the genetic risk factors for RM. For instance, Kwon et al (2022) evaluated 388 patients with RM and 280 controls in Korea and revealed that the rs10515478 C>G polymorphism of the SMAD5 gene and the rs1046875 G>A polymorphism of the fructosamine 3 kinase‐related protein (FN3KRP) gene are associated with a lower risk of RM. A study conducted by Talwar et al (2022) suggests that the 844INS68 polymorphism of cystathionine beta‐synthase (CBS) combined with the A2756G polymorphism of 5‐methytetrahydrofolate‐homocysteine methyltransferase (MTR) is associated with over 2‐fold increased RM risk.…”
Section: Current Opinions On Rmmentioning
confidence: 99%